Q: Solve 6 minus 3x equals 4 minus 2x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

You fill in for x and solve the equation3(5)^2 - 2(5)15^2 - 10; now solve

(3x + 1) = -3 (x + 2x -1) (3x + 1) = -3 (3x - 1) 3x + 1 = -9x + 3 12x = 2 6x = 1 x = 0.16666666666666666666666666666666666666666666666666666666666666666666

3x-y=9 y=3x-9

3x2 - 2x - 5 = (3x - 5)(x + 1) = 0 gives a solution of x = 5/3 or -1. Was that what you wanted?

Related questions

3x=2x-12x=-12

3x - 2x + 4 = 0 3x - 2x = -4 x = -4

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

3x+7=2x-5 x=-12

3x+4 = 2x-3 3x-2x = -3-4 x = -7

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

3x-2 = 2x+3 3x-2x = 3+2 x = 5

-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3

6 - x + 7 - 3x - 5 = -2x - 10 ∴ x + 3x - 2x = 6 + 7 - 5 + 10 ∴ 2x = 18 ∴ x = 9

2x+3y=13 3x-y=3 x=2

You fill in for x and solve the equation3(5)^2 - 2(5)15^2 - 10; now solve

An equation where x equals 3.